Faktor-Faktor Yang Mempengaruhi Tax Avoidance (Study Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Tahun 2014-2018 - Warseno Warseno; Silpi Intan Suseno; Widya Febriani (IJAcc, 2020)
This study aims to determine the effect of Profitability, Leverage, Firm Size and Institutional Ownership on Tax Avoidance in Manufacturing Companies in the Basic and Chemical Industrial Sector in 2014-2018. The variables used in this study are profitability, leverage, company size and institutional ownership, while the dependent variable used is tax avoidance which uses an effective tax rate proxy. The analysis technique used in this study is multiple linear regression analysis where previously the data were tested using a classic assumption test consisting of normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The results showed that partially Profitability affects tax Avoidance. Simultaneously Profitability, Leverage, Firm Size and Institutional Ownership affect tax avoidance. The contribution of the dependent variable in explaining the independent variable is only 12.6%.